Antiproliferative effects of α-tomatine are associated with different cell death modalities in human colon cancer cells. (December 2016) - Rudolf, Kamil; Rudolf, Emil
Highlights: α-Tomatine is a potent antiproliferative agent in colon cancer cells. α-Tomatine stimulates lysosomal membrane damage. α-Tomatine causes mitochondrial release of AIF in the absence of oxidative stress. α-Tomatine induces both necroptosis as well apoptosis. Abstract: Antitumour effects of α-tomatine were studied during 24 hours in a panel of human colon cancer cells. α-Tomatine proved to induce dose-dependent cytotoxicity resulting in morphologically varying cell demise with predominantly occurring necrotic phenotypes and minor presence of cells dying via caspase-independent apoptosis. Analyses into the nature of mechanisms responsible for activation of cell death revealed that following α-tomatine treatment, changes in RIP3 and RIP1 protein expression take place along with cyclophilin D mitochondrial accumulation. Moreover, in treated cells, lysosomal membrane permeabilization as well as mitochondrial perturbation with subsequent mitochondrial release of apoptosis-inducing factor (AIF) contributes to the execution of diverse death phenotypes possibly via enhanced activity JNK but in the absence of significant oxidative stress. Thus α-tomatine exhibits significant antitumour activity in colon cancer cells via targeting their membranous compartments and inducing both necroptosis and apoptosis.